Sequence variation at ANAPC1 accounts for 24% of the variability in corneal endothelial cell density - Erna V. Ivarsdottir (Nature Portfolio, 2019)
The corneal endothelium is crucial for proper vision. Here, Ivarsdottir et al. perform genome-wide association studies for various corneal endothelial cell measurements and find that an intergenic variant near ANAPC1 explains 24% of the variance of endothelial cell density and associates with corneal hysteresis.